RELATIONSHIP BETWEEN KNOWLEDGE OF POSTPARTUM MOTHERS AND THE IMPLEMENTATION OF POSTPARTUM EXERCISES: RELATIONSHIP BETWEEN KNOWLEDGE OF POSTPARTUM MOTHERS AND THE IMPLEMENTATION OF POSTPARTUM EXERCISES - Sellia Juwita Juwita (Jurnal Ilmu Kesehatan Abdurrab, 2025)
Data from the Indonesian Ministry of Health shows that the number of maternal deaths in 2022 caused by eclampsia is 23% and bleeding is 20%. In 2023, the cause of death due to eclampsia is 24% and postpartum bleeding is 23%. The postpartum period is the period after a mother gives birth to a baby which is used to restore her health which generally takes 6-12 weeks. Postpartum gymnastics helps heal the uterus, abdomen, and hip muscles that have been traumatized and accelerates the return of these parts to their normal shape, helps normalize joints that have become loose due to pregnancy and childbirth and prevents further weakening and stretching, produces psychological benefits, increases the ability to deal with stress and relax so as to reduce postpartum depression. The purpose of this study was to determine the relationship between maternal knowledge about postpartum excercises and the implementation of postpartum excercises in the Payung Sekaki Health Center Work Area. The research design used in this study was quantitative with a cross-sectional approach. The population in this study were postpartum mothers with an accidental sampling technique with a sample size of 45 people. Data analysis using univariate analysis and bivariate analysis using the chi-square test. The results of the univariate analysis obtained that the knowledge of respondents who had sufficient knowledge was 44.4% and had good knowledge 55.6%. Implementation of postpartum gymnastics 46.7% of respondents who did not do postpartum excercises and 53.3% of respondents did postpartum excercises. Statistical tests using Chi-Square produced a value of p = 0.001 (p <0.05), which showed that there was a significant relationship between maternal knowledge about postpartum excercises and the implementation of postpartum excercises. The better the mother's knowledge, the better the reception of information received, so that the mother can receive information. With good knowledge, it is expected that postpartum mothers will do postpartum excercises.